Desejo de memória: a história e a memória da reserva florestal do Morro Grande e da Vila Operária do DAE - Noseda, Vilma Cristina Soutelo Assunção (2023)
The research aims to reflect on the history and memory of the existing cultural heritage in the neighborhood of Morro Grande, in the municipality of Cotia (São Paulo), where the Morro Grande Forest Reserve is located, listed by CONDEPHAAT, in the 1980s. In order to meet the demand of the community concerned about urban speculation, deforestation and the loss of its local collective memory, we carried out the participatory inventory and collective production of the documentary Desires of Memory – the History of Vila DAE and the Forestry Reserve of Morro Grande It is based on the new museology and through their own narratives of memories that we involve the community, when we carry out the participatory inventory, a process in which communities assume, in the first person, the identification, selection and recording of the most significant cultural references for their memories and social histories. In the field of Museology, the resource makes it possible to establish dialogues between people, in order to identify the aspects to be patrimonialized by the community, as well as to jointly propose products that disseminate memory actions. Within the scope of the participatory inventory, we held meetings with the community that we call Memory Wheels, which made it possible to address issues that pervade the themes: memory, culture, heritage, cultural policies, museum and citizenship. With the intention of valuing and equipping the community and providing conditions to reverse the situation of underutilization of the region's cultural heritage. It is worth remembering that the Covid 19 pandemic brought many challenges, including that of involving the community at a time when the social isolation that was necessary as a measure to contain the pandemic. The report presents digital platforms and social networks and the elaboration of the documentary as allied tools of Environmental and Heritage Education that allowed us to overcome these obstacles